Evaluation of Catheter Infection Rates in Converted Dialysis Catheters versus de Novo Placement in the Setting of Chlorhexidine Use. Issue 2 (March 2016) - Criddle, Jared M.; Hieb, Robert A.; White, Sarah B.; Patel, Parag J.; Hohenwalter, Eric J.; Tutton, Sean M.; Rilling, William S.
Purpose: Prior studies have reported infection rates of converting non-tunneled dialysis catheters (NTDCs) to tunneled dialysis catheters (TDCs) versus de novo placement of TDCs using povidone-iodine. Chlorhexidine, per the Center of Disease Control guidelines, has been exclusively used in our institution since 2005. Therefore, our study aims to determine whether there is a difference in infection rates between conversion and de novo placement when utilizing chlorhexidine. Materials and Methods: A retrospective analysis from 1/1/2009 to 8/10/2012 was performed of patients who underwent placement of NTDCs, which were subsequently converted to TDCs and those who underwent de novo TDC placement. To assess the rate of infection, the following data points were collected: date of procedure(s), indication, outcomes, site of catheter insertion, pre- and post-procedure laboratory values, complications, infection rates within the life of the initially placed catheter, catheter days, and survival. Results: The conversion cohort was composed of 205 patients, 135 of whom were lost to follow-up, leaving 70 patients. The de novo cohort included 70 randomly selected patients. Of the 70 patients who underwent conversion, 23 developed a catheter-related infection, with an infection rate of 0.26 events per 100 catheter days. Of the 70 de novo catheters, 20 developed infection with an infection rate of 0.25 events per 100 catheters days. Conclusion: In this series, there is no difference in infection rates between conversion and de novo TDC placement when utilizing chlorhexidine as the sterilization agent. However, these infection rates are superior to those reported when using povidone-iodine.